Contested public organizations. Coordination, strategy and the increasing importance of knowledge. Some lessons from current research and avenues for future research. - Fuhr, Harald (Budrich, 2016)
Obwohl öffentliche Organisationen heute eine Vielzahl an vertrackten Policy-Problemen zu bewältigen haben und unter erheblichem Leistungsdruck stehen, hat die Forschung sich bislang kaum mit der Frage beschäftigt, wie sich diese Organisationen konkret den Herausforderungen stellen und wie sie hierzu entsprechende Managementaufgaben übernehmen. Unsere eigene Forschung versuchte, diesen Mangel zu beheben und untersuchte in den letzten Jahren, wie öffentliche Organisationen Wissen generieren, auswählen und nutzen, Akteure und Prozesse koordinieren und angemessene Strategien entwickeln, um derartige vertrackte Probleme wirkungsvoll anzugehen und gleichzeitig Legitimität zu erhalten. Während die drei gewählten Reaktionsformen - Wissen, Strategie und Koordination - analytisch differenzierte Ergebnisse lieferten, plädiert dieser Artikel indes dafür, sich stärker mit der wachsenden und sich ausweitenden Bedeutung von Wissen und Information für Koordinations- und Strategieprozesse auseinanderzusetzen. Angesichts eines zunehmenden Gewichts evidenz-basierter Entscheidungsprozesse in öffentlichen Organisationen, der allgegenwärtigen Verfügbarkeit von Daten und Informationen, einer rasch voranschreitenden Digitalisierung und eines starken gesellschaftlichen Drucks, sowohl Informationen zu sichern als auch über Verwaltungshandeln bereitzustellen, ergibt sich ein interessanter neuer Kontext.

Although today s public administrations need to deal effectively with a variety of wicked problems and pressure on their performance is high, understanding the underlying features of how public administrations respond, and how organizational adaptation and management occur, has so far received little attention in academic research. To attempt to address this shortcoming, our own research over the past few years has focused on the capacity and ability of public administrations to generate, select and use knowledge; to coordinate actors, processes, and resources; and to define appropriate strategies for a variety of organizational challenges in order to deal with such problems and maintain legitimacy. While these three key responses knowledge, strategy and coordination have sharpened our analysis, this article highlights the need to focus more strongly on the growing significance of information and knowledge for processes of coordination and strategizing. Given the increasing importance of evidenced-based decision making in public organizations, the ubiquitous availability of data and information, the rapid pace of digitalization, and strong societal demand to provide and secure information about administrative action, this article suggests that we need to take a much closer look at the capacities and capabilities of administrations to successfully acquire, process and supply knowledge.
Keywords: Verwaltung; Verwaltungshandeln; Verwaltungsorganisation; Information; Informationstechnologie; Management; Wissenstransfer